Religio-Cultural Festivals of India - V.F. Vineeth (Journal of Dharma, 1987)
Man is living in this world of time and is looking forward to transcend time participating in the world of gods. Everything in this world is characterised by finitude and therefore man's desire to transcend time is actually to enter into that state of existence beyond time, the time of gods, the so-called sacred time.' For this purpose man creates mythological time in which he brings god down from the sacred time and he himself ascends from the ordinary time.